Utilization of Organic Waste into Environmentally Friendly Household Cleaning Agents: Eco-Enzyme - Rapita Purba; Gabriel Sontaria Manalu; Siti Patimah; Hilfi Pardi (Jurnal Perkotaan, 2024)
Waste is one of the major problems in terms of preserving the natural environment for humans. When waste is produced in large quantities, improper management will endanger human health and the environment. Making Eco-Enzyme (EE) products from waste, especially organic waste from homes, is one possible answer. Since Eco-Enzyme is made by fermenting organic waste using brown sugar as a substrate, it can be produced on a small scale. The aim of this project is to find out the advantages of producing Eco-Enzyme products from household organic waste, especially fruit and vegetable waste. This experiment uses the method of literature review and simple experimentation. The result of this experiment is an Eco-Enzyme product that is used as a disinfectant, a mixture of floor cleaning detergents, a pesticide residue cleaner, a descaler and a decrease in car radiator temperature, a hand-sanitizer (hand sanitizer) and also a skin wound medicine.